(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
A 6 year old boy presented with sign symptoms of cerebral stroke. After clinical and radiological evaluation, a diagnosis of bilateral moyamoya disease was made. An indirect bypass surgery encephaloduroateriosynangiosis was done on the right side at first then on the left side. Patient was partially improved. At one year follow-up, there was the evidence of occlusion of collateral circulation on the right side and the patient became symptomatic again. It is noted that, although the early indirect bypass surgery is indicated in the pediatric patients for preventing the stroke but the outcome is difficult to judge.